Evaluating purple passion fruit (Passifloraedulis Sims f. edulis) genetic variability in individuals from commercial plantations in Colombia - Ortíz, Diana Carolina; Bohórquez Cháux, Adriana; Duque E., Myriam Cristina; Tohme, Joseph M.; Cuéllar, David; Mosquera Vasquez, Teresa (Springer, 2012)
This study evaluated P. edulis f. edulis intraspecific variation at DNA level using AFLPs and SSRs. About 60 specimens were collected from Colombian commercial plantations in the departments of Antioquia, Boyacá, Cundinamarca, Huila, Quindío and Tolima. Ten specimens were also included from Corpoica’s La Selva research center Passiflora germplasm bank. A non-commercial purple passion fruit plant and three species from the Passiflora genus (Passiflora maliformis, Passiflora edulis f. flavicarpa and Passiflora ligularis) were included as controls. The six most informative ones were selected from the initial screening of 49 different AFLP primer combinations; 52–92 DNA fragments for each combination in each genotype (total 419 fragments) were obtained by using these six combinations. 17 SSR primers reported in P. edulis f. flavicarpa and Passiflora alata were tested on purple passion fruit. Eight of them were successfully amplified but none showed polymorphism. Relationships among individuals were assessed on AFLP data using cluster analysis by Dice coefficient, UPGMA algorithm and the multiple correspondence analysis ordination method based on Greenacre measurement. The similarity coefficients ranged from 0.75 to 1.00 giving an average of 0.96 within the different purple passion fruit materials, showing low genetic variability for the purple passion fruit material used in this study.